Vegetation trend after roller chopping and native grass seeding in La Rioja (Semiárida, 2020)
In La Rioja plains, roller chopping and buffelgrass seeding is a widespread strategy for forage rec uperation of deg raded rangelands. Native grass species seeding arises a s apossible alternative strategy. The purpose of this study was to evaluate the medium time impacts of roller chopping and roller chopping + native species seeding on grass forage yield, cover and density and woody cover in degraded sites of critic environments of the mentioned region. Four treatments were evaluated, T0=control, T1=Roller chopping, T2= Roller chopping+Trichloris crinite (Lag.) Parodi seeding and T3= Roller chopping+Trichloris crinite (Lag.) Parodi and Pappophorum vaginatum Phil. seeding on three degraded environments. T1, T2 y T3 produced important increments (p
Keywords: Rangeland rehabilitation; mechanical treatment; native grass seeding; forage Yield; grass cover; woody cover